Microscopy applied to biofilms in drinking water closed loop - Rosales, Blanca Margarita (2011)
During water distribution operation, tubing material is submitted to permanent contact with aquatic microbial species. They colonise the network surface forming biofilms which frequently cause corrosion on metallic substrata. The present study approaches the analyses of laboratory biofilms formed on water pipe materials from several (SEM, ESEM, CLSM) microscopy technique point of view and also from a microbial ecological analysis using DGGE for the study of the communities formed on each substrate. Microbial interactions with the different materials were described using an ample range of magnification. Three commercial metals (Fe, Zn, Cu) and polypropylene tubing used as substrata revealed very different behaviours. Even when it was possible to distinguish different attack morphologies and the biofilms 3-D structures formed on all materials it was not already established a clear correlation with the genetic profile of each community.